Formulasi dan uji aktivitas antibakteri sediaan spray mikroemulsi ekstrak daun pepaya (Carica papaya L.) terhadap Staphylococcus epidermidis - Leny Leny; Siti Fatimah Hanum; Sariyah Nur Eka Wati; Lilis Sundari (Health Sciences and Pharmacy Journal, 2020)
Papaya leaves (Carica papaya L.) contain antibacterial compounds, based on previous studies, the antibacterial active substances in papaya leaves have been tested against several bacteria from in vitro method. Papaya leaves contain tannins, alkaloids, flavonoids, saponins and terpenoids. The purpose of this study is to formulate a microemulsion preparation from papaya leaf extract and to determine the effect of papaya leaf extract microemulsion preparation on the antibacterial activity of Staphylococcus epidermidis. This research was done by making microemulsions of papaya leaf extract at 5% (F1), 10% (F2) and 15% (F3) concentration, which were then tested for organoleptic test, homogeneity test, microemulsion type, stability, pH value, particle size analyzer and bacterial inhibition test by using the well diffusion method. The results showed that all preparations met the requirement of physical characteristics of microemulsion and was stable during accelerated stability test. The result of inhibition test against Staphylococcus epidermidis showed that F1 and F2 had moderate inhibition, F3 had a strong inhibitory power which is 10,1 mm.